Cytological and Histological Correlation of Medullary Carcinoma of Thyroid Based on Bethesda System for Reporting Thyroid Cytology: A Single Center Experience - Faiz, Muhammad Fahad; Loya, Asif; Hameed, Maryam Amjad; Syed, Madiha; Sheikh, Umer Nisar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The cytological evaluation of thyroid carcinoma is a diagnostic tool with additional benefits of accuracy, being minimally invasive and cost-effective. However, a histological correlation is necessary to affirm its effectiveness in case of medullary carcinoma thyroid. Aim: To evaluate the correlation between cytological and histological findings in cases of medullary carcinoma of the thyroid. Methods: Retrospective study. Shaukat Khanum Memorial Cancer Hospital (SKMCH) from 1st December 2021 to 30th June, 2022. Thirty patients were sought who underwent cytology as well as histopathology after surgery. The data of fine needle aspiration cytology and the corresponding information were sought from the hospital archives. The Bethesda categorization was done according to the cytological appearance. Data after the histopathological analysis was also sought. Results: Most of the patients 53.3% were females. Twenty out of these were diagnosed as medullary carcinoma. 93.3% of the Bethesda category IV were diagnosed as medullary carcinoma (p=0.000). The majority of category IV FNAs were also adequate for performing tumor markers (p=0.00). Practical Implication: The study highlights the high incidence of medullary carcinoma in Bethesda Category IV thyroid nodules, with 93.3% being diagnosed. The majority of patients are female, highlighting the need for vigilance. The majority of fine needle aspirations (FNAs) for these nodules were adequate for performing tumor markers, indicating their reliability for diagnosis and treatment planning. The findings underscore the importance of thorough diagnostic procedures for this high malignancy rate. Conclusion: The cytological categories of Bethesda have strong association with diagnosis of medullary carcinoma thyroid especially if category IV is diagnosed, there are high chances carcinoma may turn out to be medullary carcinoma.